1995
DOI: 10.1007/bf01088440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali treatments on the nutritive value of common bean (Phaseolus vulgaris)

Abstract: The effect of alkali treatments of common bean seeds with red seed coat on the stability of antinutritional factors such as tannins, phytates and trypsim inhibitors, vitamins such as niacin and riboflavin and on protein quality has been studied. The samples were processed by soaking and pressure cooking in alkalies such as sodium hydroxide, sodium carbonate and sodium bicarbonate. At low temperature sodium carbonate and at high temperature sodium bicarbonate were found to be most effective in the extraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Another beneficial effect was observed by Jyothi and Sumathi (1995), who found that exposure of the common bean (Phaseolus vulgaris) to NaHCO 3 , Na 2 CO 3 , and NaOH enhanced digestibility and biological value (BV) of the beans. These effects result from extraction and/ or inactivation of antinutritional tannins, phytates, and trypsin inhibitors and release of bound vitamins niacin and riboflavin.…”
Section: Nutrition and Safetymentioning
confidence: 93%
“…Another beneficial effect was observed by Jyothi and Sumathi (1995), who found that exposure of the common bean (Phaseolus vulgaris) to NaHCO 3 , Na 2 CO 3 , and NaOH enhanced digestibility and biological value (BV) of the beans. These effects result from extraction and/ or inactivation of antinutritional tannins, phytates, and trypsin inhibitors and release of bound vitamins niacin and riboflavin.…”
Section: Nutrition and Safetymentioning
confidence: 93%
“…Trypsin inhibitors are heat-labile and can be partially or completely denatured when exposed to elevated temperature. Jyothi and Sumathi (1995) reported that the extraction at both low and high temperatures with sodium bicarbonate was most effective in the case of trypsin inhibitors of common bean seeds.…”
Section: Figure 2: Trypsin Inhibitor Activity (Mg/g On Dry Weight Basmentioning
confidence: 99%
“…A study on the effects of cooking methods on thiamin and riboflavin contents of chicken meat shows that riboflavin was well retained (46-94%) in cooked broiler meat (Al Khalifa & Dawood, 1993). Alkali treatments of common bean (Phaseolus vulgaris) followed by cooking, retained the maximum amount of riboflavin and niacin as compared to other vitamins (Jyothi & Sumathi, 1995). c-irradiation of meat products showed no loss of riboflavin (Fox, Lakrits, & Thayer, 1997;Fox et al, 1995).…”
Section: Introductionmentioning
confidence: 97%